2010
DOI: 10.1111/j.1530-0277.2010.01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of Subjects With No Heavy Drinking Days: Evaluation as an Efficacy Endpoint for AlcoholClinical Trials

Abstract: PSNHDD appears to be a clinically informative end point measure, especially when used with a grace period, and is as sensitive as most traditional outcome measures in detecting differences between the medication and placebo groups. Nonetheless, these findings should be replicated in other clinical data sets, particularly with medications that work via different mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
161
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(171 citation statements)
references
References 17 publications
(27 reference statements)
6
161
0
4
Order By: Relevance
“…Grace periods, or a priori-defined periods of time during which any drinking is not included into statistical analyses of treatment outcomes, is supported by a recent study from the COMBINE data set that reported heavy drinking during the final 8 weeks of treatment was predictive of drinking at post-treatment follow-up visits (Gueorguieva et al, 2015). Employing grace periods to refine primary outcome analyses in alcohol treatment trials has been endorsed by NIAAA (Falk et al, 2010) and the Food and Drug Administration (FDA) (FDA, 2015), and represents an acknowledgment that it may take time for a medication to begin exerting an effect on drinking patterns or for patients to become stable in their treatment regimen. Additional research that assesses the degree to which early drinking behavior may relate to drinking that occurs after a prespecified grace period would be of great value.…”
Section: Discussionmentioning
confidence: 90%
“…Grace periods, or a priori-defined periods of time during which any drinking is not included into statistical analyses of treatment outcomes, is supported by a recent study from the COMBINE data set that reported heavy drinking during the final 8 weeks of treatment was predictive of drinking at post-treatment follow-up visits (Gueorguieva et al, 2015). Employing grace periods to refine primary outcome analyses in alcohol treatment trials has been endorsed by NIAAA (Falk et al, 2010) and the Food and Drug Administration (FDA) (FDA, 2015), and represents an acknowledgment that it may take time for a medication to begin exerting an effect on drinking patterns or for patients to become stable in their treatment regimen. Additional research that assesses the degree to which early drinking behavior may relate to drinking that occurs after a prespecified grace period would be of great value.…”
Section: Discussionmentioning
confidence: 90%
“…Además, estudios recientes han confirmado la relación entre el número de días que el paciente supera dicho límite y la cantidad de consecuencias negativas del consumo de alcohol 10 .…”
Section: Consumo De Riesgo Y Gravedad De La Dependencia Del Alcoholunclassified
“…El estudio COMBINE, efectuado en Estado Unidos 19 , compara diversas modalidades de tratamiento farmacológico y psico-social del alcoholismo y concluye que uno de los indicadores más útiles del resultado del tratamiento es el núme-ro de días de consumo excesivo ("heavy drinking days") que ha tenido el paciente a lo largo de todo el tratamiento, ya que este indicador tiene una buena correlación con la cantidad de consecuencias (relacionadas con el consumo de alcohol) que ha sufrido cada paciente durante el tratamiento e incluso durante su seguimiento posterior 10 . Esta correlación sugiere que si un paciente consigue mantener un consumo de alcohol que no alcance las 5 consumiciones en un día (si es un hombre), 4 si es una mujer, presentaría prácticamente la misma cantidad de consecuencias negativas, (relacionadas con el consumo excesivo de alcohol), que la persona que ha dejado de tomar bebidas alcohólicas.…”
Section: Pharmacological Treatment Of Alcoholismunclassified
See 2 more Smart Citations